Comparison of overexploitation of Bauru Aquifer in the years 2002 and 2012 (Research, Society and Development, 2020)
The urbanization process, in addition to transforming the characteristics of the natural landscape and promoting impacts on the environment, directly interferes with soil parameters, especially hydrological ones, such as waterproofing, reducing the conditions of infiltration and recharge of underground water sources. Excessive exploitation of groundwater already poses risks to public supply in some Brazilian municipalities, requiring the implementation of appropriate management methods to ensure the sustainable use of this water resource. This work aimed to identify the lowering of the potentiometric level in the period from 2002 to 2012 of an area of ​​227 km² of the Bauru Aquifer located in the central region of the Municipality of São José do Rio Preto - SP. For this, data were collected from 625 wells in the SIAGAS (Groundwater Information System) and in the DAEE (Department of Water and Electricity) in Araraquara. To analyze the data, a geostatistical analysis was performed using the Surfer software. There was a decrease of 0.47 m year-1 in the potentiometric level of the study area, due, among other factors, to an intense increase in well drilling.